THE EFFECT OF BIVALVE Semele sp. MEAT CONSUMPTION ON ESTROGEN LEVEL AMONG THE PEOPLE OF MUNA REGENCY, SOUTHEAST SULAWESI - Sjafaraenan Sjafaraenan (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2013)
A study on the influence of bivalve Semele sp meat consumption on estrogen level among the people of Muna Regency, Southeast Sulawesi, was conducted in Lasalepa Village, Bonea Subdistrict, Muna Regency, Southeast Sulawesi. This study was aimed to: (1) determine the nutritional content of bivalve Semele sp meat, (2) compare the estrogen levels between women that consume Semele sp meat and those that do not. This study was an experimental study with one group pre-test and post-test. Subjects consisted of 20 women in the age range of 40-55 years old. Subjects consumed raw Semele sp meat in the amount of 400-500 g three times in a week for one month. Blood samples were collected through cubital median vein, before and after bivalve consumption. Protein content was measured by Kjeldhal method, carbohydrate by Anthron method, fat by gravimetry, mineral by AAS, and estrogen by ELISA technique. Study findings indicated that (1) the protein content was 7.182%, carbohydrate 66.87%, fat 6.82%, cholesterol 10mg/dL, calcium 263.385 ppm, cuprum 9.107 ppm, magnesium 28.467 ppm, ferum 1,859 ppm, zinc was undetectable, (2) there was a significant difference in estradiol and estron levels before and after bivalve consumption in the three age groups, 17,022 pg/mL and 51.018 pg/mL, (3) there was no significant difference in estriol level before and after bivalve consumption in the three age groups.